BIAK LANGUAGE GREETINGS AND THEIR IMPLICATIONS FOR LOCAL LANGUAGE LEARNING IN SCHOOLS - Yesika Ohorella; Kamajaya Al Katuuk; Susan Monoarfa (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2023)
The objectives of this research are to describe Biak language greeting words in terms of form and meaning and their implications for local language learning in schools. The method used in this research is descriptive qualitative method. To collect data, the techniques used are observation, listening technique and conversation technique. To analyze the data, the technique used is qualitative analysis technique which includes: 1) Data reduction, namely simplifying the data that has been collected. 2) Presentation of data, namely, presenting data before being simplified through data grouping. 3) Verification, namely checking the accuracy of the data that has been presented. Conclusion, namely drawing conclusions to answer research questions. The results showed: 1) Family greetings: kamam (father), awin (mother), ɛba (brother), ɛknik (younger brother); 2) Kin greetings: mansar (grandfather), insar (grandmother), mɛ (aunt), kabor (nephew), insos (niece), ɛbaya kabor (male cousin), ɛbaya insos (female cousin); 3) Non-relative greetings: /ambɛr beba/ someone who has a position and is older, younger, and so on, /manan wir (community leader), manan wir bɛba (traditional leader). 4) Common greetings: kamam (father), awin (mother), kabor (a man of the same age or younger), insos (a woman of the same age or younger). The implication of this research can be applied in local language learning in schools to better understand and appreciate local culture and grammar.